2021
DOI: 10.1177/00220345211015948
|View full text |Cite|
|
Sign up to set email alerts
|

Sources of SARS-CoV-2 and Other Microorganisms in Dental Aerosols

Abstract: On March 16, 2020, 198,000 dentists in the United States closed their doors to patients, fueled by concerns that aerosols generated during dental procedures are potential vehicles for transmission of respiratory pathogens through saliva. Our knowledge of these aerosol constituents is sparse and gleaned from case reports and poorly controlled studies. Therefore, we tracked the origins of microbiota in aerosols generated during ultrasonic scaling, implant osteotomy, and restorative procedures by combining revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 46 publications
6
72
0
4
Order By: Relevance
“…New methods, such as vaporized hydrogen peroxide and ultraviolet irradiation, have been proposed to decontaminate FFP2 masks [40], although promising, the evidence of their effectiveness remains limited [41]. Furthermore, there has been encouraging evidence on the actual risk of respiratory pathogens during aerosol-generating procedures [42]. Saliva may be not considered a potential source of disease transmission during the aerosol-generating procedures, and a high-volume suction capacity air volume of 150 mm Hg or 325 L/min may be sufficient to eliminate viral contamination of the surrounding environment [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…New methods, such as vaporized hydrogen peroxide and ultraviolet irradiation, have been proposed to decontaminate FFP2 masks [40], although promising, the evidence of their effectiveness remains limited [41]. Furthermore, there has been encouraging evidence on the actual risk of respiratory pathogens during aerosol-generating procedures [42]. Saliva may be not considered a potential source of disease transmission during the aerosol-generating procedures, and a high-volume suction capacity air volume of 150 mm Hg or 325 L/min may be sufficient to eliminate viral contamination of the surrounding environment [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Increased transmission in oral health care settings cannot be ruled out 11 . Viral particles can be detected in both saliva 12 and gingival crevicular fluid (GCF) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent case report, even in the presence of SARS-CoV-2 from a throat swab, SARS-CoV-2 RNA was not detected from the oral mucosal tissue; therefore, the true risk of COVID-19 infection from oral tissues cannot be confirmed [13]. A recent paper on the origin of microbes of aerosol that occurred during dental treatment showed that SARS-CoV-2 was detected in the saliva of asymptomatic COVID-19 patients, but not in the aerosol [14]. However, it is needed to be emphasized that saliva is known to contain SARS-CoV-2 RNA and the oral cavity is regarded as the main infection transmission route [15].…”
Section: Discussionmentioning
confidence: 99%